The role of polymorphism in various potential genes on polycystic ovary syndrome susceptibility and pathogenesis - Hiral Chaudhary; Jalpa Patel; Nayan K. Jain; Rushikesh Joshi (BMC, 2021)
Abstract Polycystic ovary syndrome (PCOS) is the most common endocrinopathies affecting the early reproductive age in women, whose pathophysiology perplexes many researchers till today. This syndrome is classically categorized by hyperandrogenism and/or hyperandrogenemia, menstrual and ovulatory dysfunction, bulky multi follicular ovaries on Ultrasonography (USG), and metabolic abnormalities such as hyperinsulinemia, dyslipidemia, obesity. The etiopathogenesis of PCOS is not fully elucidated, but it seems that the hypothalamus-pituitary-ovarian axis, ovarian, and/or adrenal androgen secretion may contribute to developing the syndrome. Infertility and poor reproductive health in women's lives are highly associated with elevated levels of androgens. Studies with ovarian theca cells taken from PCOS women have demonstrated increased androgen production due to augmented ovarian steroidogenesis attributed to mainly altered expression of critical enzymes (Cytochrome P450 enzymes: CYP17, CYP21, CYP19, CYP11A) in the steroid hormone biosynthesis pathway. Despite the heterogeneity of PCOS, candidate gene studies are the widely used technique to delineate the genetic variants and analyze for the correlation of androgen biosynthesis pathway and those affecting the secretion or action of insulin with PCOS etiology. Linkage and association studies have predicted the relationship between genetic variants and PCOS risk among families or populations. Several genes have been proposed as playing a role in the etiopathogenesis of PCOS, and the presence of mutations and/or polymorphisms has been discovered, which suggests that PCOS has a vital heritable component. The following review summarizes the influence of polymorphisms in crucial genes of the steroidogenesis pathway leading to intraovarian hyperandrogenism which can result in PCOS.